Research on entrepreneur identification - Giriūnas, Lukas; Giriūnienė, Gintarė (Buhalterinės apskaitos teorija ir praktika, 2014)
Recently entrepreneurship, promotion of it, development of support programmes for the creation and development of entrepreneurial entities is becoming a very common subject of not only scientific research. Thus, not every self-employed person or company, in its run or planned activities, can adopt or implement and develop entrepreneurship. So, not every business entity can distinguish for its entrepreneurship, therefore, one of the issues addressed in scientific literature is precisely identification of an entrepreneurial entity. Some researchers point out that an entrepreneurial entity is characterized by development, implementation, and enhancement of innovations, while others oppose to such a statement emphasizing that most attention should be given not to implementation of innovations, but to the preference for an aggressive market strategy. So, the article analyses the concept of an entrepreneurial entity and its features, and the main goal of the research is becoming an entrepreneurial entity identification. Analysis of the scientific literature suggests that not all entities can be called or considered entrepreneurial ones. Not all businesses, that employ the services of incubators, business information centres, technology parks, science parks, innovation centres, or other similar organizations, become entrepreneurial, so there can be no equality. Therefore, in order to consider an entity as entrepreneurial, it must not only be proactive, enterprising, venturous, open to novelty and innovation, tending to work together with academic institutions for marketing new, innovative goods and services, have sufficient skills in business management and development, exercise a decision-making influenced management structure, but also to seek a sustainable and long-term revenue rather than short-term and high-yield, treat business processes and their management as a priority, make an active use of state support for businesses, intensively pursue tax policies, and patronize a socially responsible approach to business. It should be emphasized that an entity with all the listed features that can be named as entrepreneurial, yet, we should not forget that it must try to stay the same, i.e., must be constantly evolving and heterogeneous.